Factors affecting trust in internet banking users - Asnawati Asnawati; Muhammad Ali Akbar Fachrozi; Muhammad Pandu Utomo Majid (INOVASI, 2022)
The purpose of this study was to determine the effect of Shared Value (X1), Communication (X2), and Opportunistic Behavior Control (X3) on Internet banking users' Trust (Y). The population of this research is internet banking users in East Kalimantan. The sample selection technique in this study used purposive sampling and the number of samples obtained was 100 respondents. The object of research is all internet banking users. The data collection method in this study was by distributing questionnaires. Data analysis using multiple linear regression technique using SPSS (Statistical package for social Science) versi 24.0 tool. The results showed that Shared Value (X1), Communication (X2), and Opportunistic Behavior Control (X3) had a positive and significant influence on Internet Banking User Trust (Y).